1999
DOI: 10.1016/s0022-2275(20)32106-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of naturally fluorescent triacylglycerols from Parinari glaberrimum to detect low lipase activities from Arabidopsis thaliana seedlings

Abstract: The aim of this study was to design a convenient, specific, sensitive, and continuous lipase activity assay using natural long-chain triacylglycerols (TAGs). Oil was extracted from Parinari glaberrimum seed kernels and the purified TAGs were used as a substrate for detecting low levels of lipase activities. The purified TAGs are naturally fluorescent because more than half of the fatty acids from Parinari oil are known to contain 9,11,13,15-octadecatetraenoic acid (parinaric acid) in its esterified form. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 41 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The detection sensitivity of this coated method is, however, around 50 times lower compared to that obtained with the fluorescent assays. Beisson et al 24 set up a lipase assay using parinaric acid-containing triacylglycerols, purified from Parinari glaberrimum seed oil, and quantities as low as 0.1 ng of pure pancreatic lipase could be detected under standard conditions. Unlike the fluorescence method, which is solely based on the micellar solubilization of the free fatty acid released, the UV spectrophotometric method is based on the coated phospholipid-containing α-eleostearic acid and it can be performed without detergent, which would be convenient when assaying phospholipases sensitive to detergents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection sensitivity of this coated method is, however, around 50 times lower compared to that obtained with the fluorescent assays. Beisson et al 24 set up a lipase assay using parinaric acid-containing triacylglycerols, purified from Parinari glaberrimum seed oil, and quantities as low as 0.1 ng of pure pancreatic lipase could be detected under standard conditions. Unlike the fluorescence method, which is solely based on the micellar solubilization of the free fatty acid released, the UV spectrophotometric method is based on the coated phospholipid-containing α-eleostearic acid and it can be performed without detergent, which would be convenient when assaying phospholipases sensitive to detergents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Following hydrolysis, the binding between albumin and the free parinaric acid released corresponded to an increase in the total fluorescence intensity. The drawback of this method is, on the one hand, the susceptibility of parinaric acid to oxidation by atmospheric oxygen and, on the other hand, the need for the selected detergent to solubilize the released parinaric acid into mixed micelles …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a literature review (Beisson et al, 2001) described the screening assays for quantifying lipase activity on the principles and practical aspects of this methodological consideration. It was concluded that the pH-stat method, which enabled screening over an extended range of pH values due to the inclusion of several pH indicators, is suitable for pure lipase assays, and a method based on natural fluorescent substrates, as described in Beisson et al 1999, is more suitable for crude biological sample assays (Beisson et al, 1999).…”
Section: • Methodological Considerationsmentioning
confidence: 99%
“…Attempts have been made to measure ATGL activity using fluorogenic substrates (30) such as dibutyrilfluoresceine (31), parinaric acid (32,33), umbelliferone (34,35), resorufin (24), pyrenic compounds, and BODIPY-C12 (4,(36)(37)(38). These assays have some disadvantages, namely the compounds are spontaneously hydrolyzed at pH 8.8, are susceptible to oxidation by atmospheric oxygen (39), and are poorly hydrolyzed by lipases (38,40). Nitrobenzoxadiazole (NBD) is a better fluorophore because it is small, does not interact with colored compounds, and is insensitive to oxidation (41,42).…”
mentioning
confidence: 99%